2011
DOI: 10.1111/j.1442-2042.2011.02795.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased urethral resistance by periurethral injection of low serum cultured adipose‐derived mesenchymal stromal cells in rats

Abstract: Objectives:To evaluate the effects of a periurethral injection of low serum cultured adipose tissue-derived mesenchymal stromal cells (LASC) and to develop a new autologous cell therapy for stress urinary incontinence. Methods: F344 rats were divided into three groups as based on the periurethral injection of LASC, GAX collagen or vehicle (control). At 2 and 4 weeks after injection, leak point pressure (LPP) was measured before and after transection of the pelvic nerves. For cell tracking, LASC of green fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 25 publications
2
35
0
Order By: Relevance
“…Preliminary results demonstrated possible improvement of urine linkage in patients with SUI [52, 53], and we also confirmed myogenic differentiation of ADSC by periuretral injection in an SUI rat model [54]. In the present study, treatment of ADSC with exogenous FABP4, but not FABP5, was partially associated with myogenesis.…”
Section: Discussionsupporting
confidence: 87%
“…Preliminary results demonstrated possible improvement of urine linkage in patients with SUI [52, 53], and we also confirmed myogenic differentiation of ADSC by periuretral injection in an SUI rat model [54]. In the present study, treatment of ADSC with exogenous FABP4, but not FABP5, was partially associated with myogenesis.…”
Section: Discussionsupporting
confidence: 87%
“…Previously, the functional evaluation was usually performed after the transplantation to the directly injured 9,14,15,25 or denervated urethra. 7 In the majority of these studies, the significant improvement of urethral closure in transplanted animals was noted when compared to the injured nontransplanted groups. [4][5][6]12,13,15 The reason for the inconsistency of results is probably the lack of fresh urethra injury in the presented study.…”
Section: Discussionmentioning
confidence: 96%
“…In the last decade, numerous studies have been performed in order to test the procedure of cellular transplantations into the urethral sphincter. It was shown that different cell types, such as myoblasts, 4 muscle derived stem cells, 5 bone marrow, or adipose tissue-derived mesenchymal stem cells 6,7 can survive after the injection into the urethral wall. However, although numerous different studies were performed to examine the procedure of intraurethral cell transfer, the graft has never been administered with the use of an endoscope in animal models.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Implanted ADSCs were supposed to differentiate into skeletal muscle, smooth muscle, nerve, and endothelial cells according to their immunohistochemical analyses. Watanabe et al [70] and Wu et al [71] conducted similar experiments in a pelvic nerve injury-induced SUI model. According to their data, animals with ADSC treatment also showed significant myogenic differentiation or regeneration and improved LPP results.…”
Section: Stress Urinary Incontinence (Sui)mentioning
confidence: 99%